INFLUENCE OF SINTERING TEMPERATURE AND HOLDING TIME ON TENSILE STRENGTH AND SHRINKAGE OF PVC SPECIMEN ON INDIRECT PRESSURE-LESS SINTERING PROCESS - S. A Widyanto; S Riyadi; A. E Tontowi; Jamasri Jamasri; H. S Rochardjo (Mesin, 2006)
Sintering process has proven to be a manufacturing process that can produce a mechanical part with high geometric complexity. Development of alternative sintering process is continuously conducted to find the most inexpensive process. A solution process which is called indirect pressure-less sintering were proposed in this research. Generally this process of making a mechanical part is initiated with arranging powder by deposition machine, and continued by sintering process in conventional furnace. Optimal parameters that consist of sintering temperature and holding time in this process were optimized in this paper. PVC powder and sand casting (silica) were used as a material product and supporting powder respectively. The variations of sintering temperature are 100, 105, 110, 115 and 120°C, while the holding times are 2, 4, 6 and 8 hours. The optimal parameters were found by measuring tensile strength and shrinkage of specimen. The experiment results showed that dimensional stability of specimen can not be maintained for sintering temperature of 115°C with holding time longer than 2 hours. In sintering temperature higher than 120°C, PVC material directly starts to melt so that the volume of specimen increased. This was caused by binding of supporting powder. The strength of binding mechanism was measured when sintering temperature was higher than 107°C. In sintering temperature of 113°C with varying the holding time (2-8 hours) gave the longest variation of tensile strength.